“In vitro” evaluation of the bacterivore potential of three Cladoceran species occurring in tropical and subtropical regions - Hayashi-Martins,L. H. (2017)
Abstract Cladocerans occupy an important position among the bacterial consumers in freshwater food webs, being relatively non-selective filter feeders that can exert a strong impact on microbial populations. We evaluated the bacterivory potential of three cladocerans species of subtropical and tropical occurrence (Ceriodaphnia silvestrii, Daphnia gessneri and Ceriodaphnia cornuta) at different life stages, by scanning electron microscopy (SEM) and by the quantification of their bacterial consumption rates using fluorescently labeled bacteria (FLB). All species showed filter mesh sizes sufficiently narrow to retain bacteria. The largest distance between setules was found in primiparous C. cornuta, and the smallest in neonate D. gessneri. The lowest ingestion (IR) and removal (RR) rates were observed in primiparous C. silvestrii and the highest values were observed in adults of D. gessneri. We conclude that bacteria may be considered an important food supplement, particularly for neonates who presented smaller intersetular distances and higher filtration rates than the other life stages.